Influence of cyclosporin a therapy on bone healing around titanium implants: A histometric and biomechanic study in rabbits - Sakakura, Celso E.; Margonar, Rogério; Holzhausen, Marinella; Nociti Jr., Francisco H.; Alba, Rodolfo Candia; Marcantonio Jr., Elcio (Wiley, 2003)
Background: Immunosuppressive agents may induce severe changes on bone metabolism. The purpose of the present study was to evaluate the influence of the administration of cyclosporin A (CsA) on the bone tissue around titanium implants. Methods: Eighteen New Zealand rabbits were randomly divided into 2 groups of 9 each. The test group (CsA) received daily subcutaneous injection of CsA (10 mg/kg body weight) and the control group (CTL) received saline solution by the same administration route. Three days after therapy began, 2 implants (7.0 mm long and 3.75 mm in diameter) were inserted bilaterally at the region of the tibial methaphysis. After 4, 8, and 12 weeks the animals were sacrificed and biomechanical tests and histometrical procedures, consisting of the determination of the percentages of bone-implant contact and bone area within the limits of the implant threads, were performed. Results: Intergroup analysis showed that the removal torque and the percentage of bone contact with the implant surface for CsA group were significantly lower than those of the CTL group at 12 weeks (28.5 and 39.2 N cm, P=0.01; 7.76% and 18.52%, P=0.02, respectively). Conclusion: The data from the present study suggest that long-term administration of cyclosporin A may negatively influence bone healing around dental implants.
Keywords: Bone regeneration; Cyclosporin A/adverse effects; Dental implants; Osseointegration; Titanium; Wound healing